Black conductive silver paste for automobile glass and preparation method thereof

By using a combination of LSCO conductive ceramic powder and transition group oxide, the color problem caused by silver ion diffusion in the existing technology is solved, achieving a black aesthetic effect of the conductive layer of automotive glass, and meeting high-performance usage requirements.

CN119339988AActive Publication Date: 2025-01-21CHINA ZHENHUA GRP YUNKE ELECTRONICS
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411792783.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-07
Publication Date
2025-01-21
Estimated Expiration
2044-12-07

AI Technical Summary

Technical Problem

In the prior art, the use of transition group metal oxide colorants cannot effectively mask the color on the glass substrate. Although silver ion reducing agents and sulfides can reduce silver ions diffusion, they affect conductivity and solderability, resulting in changes in the color of the substrate. Not big.

Method used

LSCO (lanthanum strontium cobalt oxide ceramic) conductive ceramic powder is used to replace most of the silver powder, and transition group oxides are used as silver ion reducing agents to reduce the diffusion of silver ions to the glass substrate and prevent silver ions from coloring the glass substrate. At the same time, LSCO ceramic powder is black, which improves the color of the contact interface after sintering.

Benefits of technology

The interface between the conductive layer and the glass substrate is black, which improves the aesthetics of automotive glass, while ensuring conductivity, adhesion, oxidation resistance, organic solvent resistance and wear resistance, meeting the high reliability requirements of automotive glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses black conductive silver paste for automobile glass and a preparation method thereof, and belongs to the technical field of electronic paste. The conductive silver paste comprises the following components: LSCO conductive ceramic powder, flake silver powder, glass powder, an inorganic auxiliary agent and an organic carrier. The LSCO conductive ceramic powder is formed by sintering lanthanum oxide, strontium carbonate and cobalt oxide at high temperature, the glass powder is composed of low-softening-point borosilicate glass powder and high-softening-point borosilicate glass powder, and the difference between the softening point of the low-softening-point borosilicate glass powder and the softening point of the high-softening-point borosilicate glass powder is 100-150 DEG C; the inorganic auxiliary agent is a transition oxide, and the organic carrier comprises adhesive resin and an organic solvent; the preparation method comprises an LSCO conductive ceramic powder preparation method, a glass powder preparation method and a conductive silver paste preparation method. The problem that after existing silver paste is sintered on a glass substrate, the color, the adhesive force and the electrical property are difficult to consider is solved. The method can be widely applied to the technical field of consideration of automobile windshield appearance and electrical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electronic pastes, and further relates to the technical field of conductive silver pastes, and specifically, to a black conductive silver paste for automobile glass and a preparation method thereof. Background Art

[0002] As cars become more popular in Chinese families, China's auto industry has grown rapidly, and new car products have sprung up like mushrooms after rain. People have also put forward new requirements for the quality of cars. As the most eye-catching defogger heating wire and antenna on the car windshield, the brown-yellow color produced by the sintering of conductive silver paste and glass tin surface is no longer in tune with the beautiful appearance of various types of cars.

[0003] The paste for automotive glass is mainly printed on the rear windshield as a heating defrost line and communication antenna. The silver paste for automotive glass not only needs to meet the conditions of automotive glass tempering treatment (650℃±50℃ / 200s sintering, bending and rapid cooling), but also needs to meet the conditions of long-term exposure to the atmosphere under the use of the car, as well as the wiping of various detergents. Therefore, the silver paste for automotive glass not only needs to be sintered quickly at low temperature, but also has high requirements in terms of temperature shock resistance (matching the thermal expansion coefficient of glass and black glass glaze), strong adhesion to the substrate, oxidation resistance, organic solvent resistance, and wear resistance.

[0004] Silver paste for automobile glass turns brownish yellow after sintering, which has always troubled the related electronic paste manufacturers, who have always wanted to change the sintering color of the silver paste by adding inorganic colorants. For example, CN113539545A "A gray conductive silver paste for automobile glass and its preparation method" published by Shanghai Baoyin Electronic Materials Co., Ltd. uses flaky silver powder, spherical silver powder, lead-free glass powder, molybdenum trioxide and organic carrier to prepare gray silver paste with good conductivity, strong adhesion and sintering matching with glass substrate. US5296413A "Automotive glass thick film conductor paste" published by DuPont uses silver powder, two glass powders with a softening point difference of 100°C, and transition metal oxides (manganese trioxide, manganese dioxide, chromium tetroxide, vanadium pentoxide, etc.) as colorants to prepare paste for automobile glass. After sintering, the silver paste is dark brown on the tin surface of the glass. In US4728781A "Heated backlights" published by PPG Industries, silver powder, silicate glass powder, and silver ion reducing agent (chromium trioxide, stannous sulfate) are used to prepare silver paste for automotive glass. During the sintering process, the silver ions in the silver paste are reduced by trivalent chromium ions or divalent tin ions, and the reduced silver is aggregated to wrap the glass into silver colloid, which can absorb visible light and make the silver paste dark gray or black after sintering. FERRO's US6624104 uses bismuth-containing weak glass phase to prepare glass glaze paste, and Degussa's US5350718 prepares glass glaze paste by adding zinc sulfide to glass to prevent the diffusion of silver paste in the glass glaze paste, but this glass system has no effect in silver paste for automotive glass. When the silver paste is sintered on the glass substrate, the silver ions can easily diffuse into the glass substrate, causing the glass substrate to be colored. The air side of the glass is yellow, and the tin side of the glass is dark yellow or dark brown. The above-mentioned patent uses transition metal oxide colorants to improve the color of the paste, but the silver ions diffuse into the glass substrate, and the dark color of the paste cannot cover up the color on the glass substrate. The use of silver ion reducing agents and sulfides in the silver paste can reduce the diffusion of silver ions into the glass substrate, but in order to meet the conductivity and solderability of the silver paste, not too much can be added. It can only reduce the diffusion of silver ions into the glass substrate, and there is not much change in the color of the substrate after the paste is sintered.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The technical problem to be solved by the present invention is to solve the problem that the transition metal oxide colorant used in the prior art cannot cover the color on the glass substrate, and the use of silver ion reducing agent and sulfide in the silver paste can reduce the diffusion of the silver ion phase glass substrate, but affects the conductivity and solderability of the silver paste and the color of the substrate does not change much.

[0007] The inventive concept of the present invention is: using LSCO (lanthanum strontium cobalt oxide ceramic) conductive ceramic powder to replace most of the silver powder, and transition oxides as silver ion reducing agents to reduce the diffusion of silver ions to the glass substrate during the sintering process of the slurry, thereby avoiding the silver ions from coloring the glass substrate. In addition, the LSCO ceramic powder is black, so that the contact interface between the silver paste and the glass substrate after sintering is black, thereby improving the appearance of the windshield.

[0008] Silver paste for automotive glass was prepared by grinding and dispersing with a three-roll mill using flaky silver powder and LSCO ceramic powder as conductive phases, two borosilicate glass powders with different softening points of 150°C as bonding phases, transition oxide chromium trioxide as inorganic additives, and 20% ethyl cellulose pinene alcohol solution as organic carrier. After sintering, the conductive layer of the paste is black at the interface with the glass substrate, and the conductivity, adhesion, sintering matching with the substrate, oxidation resistance, organic solvent resistance, and wear resistance can meet the requirements for automotive glass use.

[0009] To this end, the present invention provides a black conductive silver paste for automotive glass. In terms of mass percentage, the components of the conductive paste are: LSCO conductive ceramic powder 40%~70%, flaky silver powder 10%~30%, glass powder 1%~5%, inorganic additives 0.2%~1%, organic carrier 30%~50%.

[0010] The LSCO conductive ceramic powder is formed by high-temperature sintering of lanthanum oxide, strontium carbonate and cobalt oxide. By mass percentage, the components of LSCO conductive ceramic are: 30% to 50% lanthanum oxide, 15% to 40% strontium carbonate, and 25% to 30% cobalt oxide. The average particle size of the LSCO conductive ceramic powder is 1.0μm to 5.0μm, and D90≤10μm.

[0011] The particle size of the flaky silver powder is 1.0 μm to 10.0 μm, and the specific surface area is 1 m 2 / g~2m 2 / g, bulk density is 2g / ml~3g / ml, and tap density is 3g / ml~4g / ml.

[0012] The glass powder is composed of low softening point borosilicate glass powder and high softening point borosilicate glass powder. The components by mass percentage are as follows: the proportion of low softening point glass is 30% to 80%, preferably not more than 50%, because the acid resistance of low softening point glass is very low, and too high a proportion affects the acid resistance of the conductive layer; the proportion of high softening point glass is 20% to 70%. The softening point difference between low softening point borosilicate glass and high softening point borosilicate glass is 100℃ to 150℃. The softening point of low softening point glass is 400℃ to 520℃, and the softening point of high softening point glass powder is 550℃ to 650℃. The composition of the low softening point glass is 60% to 75% bismuth oxide, 10% to 30% boron oxide, 5% to 20% zinc oxide, 5% to 10% silicon oxide, 3% to 10% aluminum oxide, and alkali metal oxides <5%; the composition of the high softening point glass is 50% to 65% bismuth oxide, 10% to 30% boron oxide, 5% to 20% zinc oxide, 5% to 15% silicon oxide, 5% to 15% aluminum oxide, 5% to 15% antimony pentoxide, and alkali metal oxides <3%. Alkali metal oxides can be replaced by alkali metal carbonates such as potassium carbonate and sodium carbonate, preferably sodium carbonate. The glass is smelted at high temperature and then ball-milled to 1.0 μm to 5.0 μm, and then dried for use.

[0013] The inorganic auxiliary agent is a transition oxide, including a mixture of one or more oxides selected from manganese dioxide, cobalt trioxide, vanadium pentoxide, chromium trioxide, etc., preferably chromium trioxide. The particle size of the inorganic auxiliary agent is 1.0 μm to 5.0 μm.

[0014] The organic carrier includes a bonding resin and an organic solvent. The bonding resin includes ethyl cellulose, acrylic resin, polyvinyl butyral and their derivatives, which can be used alone or in combination according to the film-forming conditions of the slurry. Ethyl cellulose is preferred. The organic solvent includes one or more of butyl carbitol, butyl carbitol acetate and pineneol. Pineneol is preferred.

[0015] The preparation method of the black conductive silver paste for automobile glass is as follows: (1) LSCO conductive ceramic powder production method: 1) Mix the raw materials, use yttrium-stabilized zirconia ball mill, yttrium-stabilized zirconia grinding balls, and water as grinding media, the ball-to-material-water ratio is 3:1:1 to 5:1:1, mix for 12 hours to 48 hours and then dry.

[0016] 2) Pre-sintering of raw materials: Use an alumina crucible with a lid to hold the raw materials to prevent excessive volatilization of zinc oxide during sintering. The pre-sintering temperature is 1000°C to 1200°C, and the holding time is 1h to 4h.

[0017] 3) Secondary ball milling: use yttrium-stabilized zirconia ball mill, yttrium-stabilized zirconia grinding balls and water as grinding media, with a ball-to-water ratio of 3:1:1 to 5:1:1, and grind until the average particle size of the powder is 1.0 μm to 5.0 μm and then dry.

[0018] 4) Ceramic sintering: the powder obtained by the secondary ball milling is granulated with PVA, and the powder is pressed into a compact block-shaped green body using a tablet press according to the sintering conditions. The green body is sintered by debinding, and the sintering temperature is 1200°C to 1400°C, and the insulation time is 1h to 4h.

[0019] 5) Crushing and grinding: use yttrium-stabilized zirconia ball mill, yttrium-stabilized zirconia grinding balls and water as grinding media, with the ball-to-water ratio of 3:1:1 to 5:1:1, grind until the average particle size of the powder is 1.0 μm to 5.0 μm, D90 ≤ 10 μm, and then dry for use.

[0020] (2) Glass powder production method: The raw materials are prepared according to the requirements of glass powder components, mixed to form glass, melted at high temperature, purified with water, and then ball-milled to 1.0μm to 5.0μm, dried and set aside.

[0021] (3) Preparation method of conductive silver paste: According to the component requirements of the conductive silver paste, the conductive porcelain powder, flaky silver powder, glass powder, inorganic additives and organic carrier are charged into a stirring device in proportion to make the components fully mixed; a three-roll mill is used to fully grind and disperse the mixed slurry; the rolled slurry is filtered to remove impurities, and then the conductive silver paste for automotive glass is prepared.

[0022] After the silver paste is sintered, the interface between the conductive layer and the glass substrate is black, and has good conductivity and strong adhesion to the substrate. It has excellent performance in terms of temperature shock resistance (matching the thermal expansion coefficient of glass and black glass glaze), oxidation resistance, organic solvent resistance, wear resistance, etc., and can meet the high reliability requirements of automotive glass. It can be widely used on automotive windshields as a conductor for heating, defrosting, defogging and communication antennas, and meets the requirements for beautiful appearance of various types of automobiles. DETAILED DESCRIPTION

[0023] The black conductive silver paste for automobile glass and the preparation method thereof, taking the conductive silver paste for automobile glass as an example, the specific implementation method is as follows: Case 1: (1) Preparation of LSCO conductive ceramic powder According to the formula in Table 1: Table 1 LSCO conductive ceramic powder formula

[0024] 1) According to the formula in Table 1, weigh the raw materials according to the total mass of 1 kg. Put the raw materials, 3 kg φ10 mm zirconium oxide grinding balls, and 1 L of water into a 5 L zirconium oxide ball mill, mix for 24 hours, and then dry.

[0025] 2) Powder pre-sintering: the materials in 1) are placed in an alumina crucible and sintered in a box furnace at a heating rate of 100°C / h, a sintering temperature of 1050°C, and a holding time of 3.5h. After sintering, the powder is cooled with the furnace.

[0026] 3) Secondary ball milling: the pre-sintered block powder was beaten into small pieces using a rubber hammer, and 3 kg of φ10 mm zirconium oxide grinding balls and 1 L of water were placed in a 5 L zirconium oxide ball mill, mixed for 48 hours, and then dried.

[0027] 4) Granulation and briquetting: use 10% PVA aqueous solution for granulation, the proportion of PVA solution is 15% of the powder, and the granulated porcelain powder is pressed into block green body by tablet press at 20MPa / 15s.

[0028] 5) Firing of porcelain powder: The green body is sintered in a box furnace. The debinding curve is: heating from 100℃ / h to 600℃, keeping warm for 6h to complete debinding, heating from 300℃ / h to 1250℃, keeping warm for 3h, and cooling with the furnace after sintering.

[0029] 6) Crushing and grinding: The fired porcelain body is crushed into large-particle powders below 100 μm using a crusher. 3 kg φ10 mm zirconium oxide grinding balls and 1 L of water are placed in a 5 L zirconium oxide ball mill and mixed for 48 h ± 12 h. The average particle size of the powder is controlled to be 2 μm to 3 μm.

[0030] (2) Preparation of glass powder According to the formula in Table 2: Table 2 Glass powder formula

[0031] (3) Preparation of organic carrier: the resin in the organic carrier is ethyl cellulose, and the organic solvent is a mixture of terpineol and butyl carbitol, with a ratio of 1:1. The ethyl cellulose, butyl carbitol and terpineol are heated and dissolved in a stirring and heating reactor until they are dissolved into a transparent state. The impurities and undissolved substances in the dissolved organic carrier are filtered out and set aside.

[0032] (4) Requirements for flaky silver powder: the parameters of flaky silver powder should meet the requirements of particle size of 1.0 μm to 10.0 μm and specific surface area of ​​1 m 2 / g~2m 2 / g, bulk density is 2g / ml~3g / ml, and tap density is 3g / ml~4g / ml.

[0033] (5) Preparation of conductive silver paste According to the formula in Table 3: Table 3 Conductive silver paste formula Table 1

[0034] According to the formula in Table 3, the raw materials were weighed according to the total mass of 1 kg, put into a stirring device for uniform dispersion, and then rolled into a conductive silver paste for automotive glass using a three-roll mill. The fineness of the paste was controlled to be less than 10 μm, and the viscosity was 20 Pa•s to 60 Pa•s.

[0035] Case 2: (1) Preparation of conductive silver paste According to the formula in Table 4: Table 4 Conductive silver paste formula Table 2

[0036] According to the formula in Table 4, weigh the raw materials according to the total mass of 1 kg. The raw materials are the raw materials in Case 1. Put them into a stirring device for uniform dispersion and then use a three-roll mill to roll them into conductive silver paste for automotive glass. The fineness of the paste is controlled to be less than 10μm and the viscosity is 20Pa•s~60Pa•s.

[0037] Case 3: (1) Preparation of conductive silver paste According to the formula in Table 5: Table 5 Conductive silver paste formula Table 3

[0038] According to the formula in Table 5, weigh the raw materials according to the total mass of 1 kg. The raw materials are the raw materials in Case 1. Put them into a stirring device for uniform dispersion and then use a three-roll mill to roll them into conductive silver paste for automotive glass. The fineness of the paste is controlled to be less than 10μm and the viscosity is 20Pa•s~60Pa•s.

[0039] Comparison of silver paste sintering performance between Case 1 and Case 3: According to the design, the conductive silver paste for automobile glass is printed on the automobile glass, and after drying, it is sintered in a chain furnace with a peak temperature of 620°C and a holding time of 200s. The performance test of the conductive silver paste after sintering is shown in Table 6.

[0040] Table 6 Performance test table of conductive silver paste for automotive glass

[0041] In summary, the conductive silver paste prepared by the technical solution of the present invention is a conductive paste which is black after sintering and has excellent performance for heating and defrosting automobile glass and signal transmission antenna.

[0042] Finally, it should be noted that the above embodiments are merely examples for the purpose of clear explanation. The present invention includes but is not limited to the above embodiments. It is not necessary and impossible to list all implementation methods exhaustively. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. All implementation methods that meet the requirements of the present invention belong to the protection scope of the present invention.

Claims

1. A black conductive silver paste for automotive glass, characterized in that: By mass percentage, the components of the conductive paste are: LSCO conductive ceramic powder 40% to 70%, flake silver powder 10% to 30%, glass powder 1% to 5%, inorganic additives 0.2% to 1%, organic carrier 30% to 50%; The LSCO conductive ceramic powder is formed by high-temperature sintering of lanthanum oxide, strontium carbonate and cobalt oxide. The components of the LSCO conductive ceramic are as follows: 30% to 50% lanthanum oxide, 15% to 40% strontium carbonate and 25% to 30% cobalt oxide by mass percentage. The average particle size of the LSCO conductive ceramic powder is 1.0 μm to 5.0 μm, and D90 is ≤ 10 μm. The particle size of the flaky silver powder is 1.0 μm to 10.0 μm, and the specific surface area is 1 m 2 / g~2m 2 / g, bulk density is 2g / ml~3g / ml, tap density is 3g / ml~4g / ml; The glass powder is composed of low softening point borosilicate glass powder and high softening point borosilicate glass powder, and the components by mass percentage are: the proportion of low softening point glass is 30% to 80%, and the proportion of high softening point glass is 20% to 70%; the softening point difference between the low softening point borosilicate glass and the high softening point borosilicate glass is 100° C. to 150° C.; The composition of the low softening point glass is: 60% to 75% bismuth oxide, 10% to 30% boron oxide, 5% to 20% zinc oxide, 5% to 10% silicon oxide, 3% to 10% aluminum oxide, and <5% alkali metal oxide; The high softening point glass is composed of 50% to 65% bismuth oxide, 10% to 30% boron oxide, 5% to 20% zinc oxide, 5% to 15% silicon oxide, 5% to 15% aluminum oxide, 5% to 15% antimony pentoxide, and less than 3% alkali metal oxides; the glass is melted at high temperature and then ball-milled to 1.0 μm to 5.0 μm; The inorganic auxiliary agent is a transition oxide, including a mixture of one or more oxides selected from manganese dioxide, cobalt trioxide, vanadium pentoxide, and chromium trioxide; the particle size of the inorganic auxiliary agent is 1.0 μm to 5.0 μm; The organic carrier includes a bonding resin and an organic solvent. The bonding resin includes ethyl cellulose, acrylic resin, polyvinyl butyral or derivatives of ethyl cellulose, acrylic resin, and polyvinyl butyral, which can be used alone or in combination according to the film-forming conditions of the slurry. The organic solvent includes one or more of butyl carbitol, butyl carbitol acetate, and pineneol.

2. The black conductive silver paste for automobile glass according to claim 1, characterized in that: The proportion of the low softening point glass does not exceed 50%.

3. The black conductive silver paste for automobile glass according to claim 1, characterized in that: The softening point of low softening point glass is 400℃~520℃, and the softening point of high softening point glass powder is 550℃~650℃.

4. The black conductive silver paste for automobile glass according to claim 1, characterized in that: The alkali metal oxide is an alkali metal carbonate, and the alkali metal carbonate is potassium carbonate or sodium carbonate.

5. The method for preparing a black conductive silver paste for automobile glass according to claim 1, characterized in that: The preparation method is: (1) LSCO conductive ceramic powder production method: 1) Mix the raw materials, use yttrium-stabilized zirconia ball mill, yttrium-stabilized zirconia grinding balls and water as grinding media, the ball-to-water ratio is 3:1:1 to 5:1:1, mix for 12h to 48h and then dry; 2) Pre-sintering of raw materials: Use an alumina crucible with a lid to hold the raw materials to prevent excessive volatilization of zinc oxide during sintering. The pre-sintering temperature is 1000°C to 1200°C, and the holding time is 1h to 4h; 3) Secondary ball milling, using yttrium-stabilized zirconia ball milling jars, yttrium-stabilized zirconia grinding balls, and water as grinding media, with a ball-to-water ratio of 3:1:1 to 5:1:1, grinding until the average particle size of the powder is 1.0 μm to 5.0 μm and then drying; 4) Ceramic sintering: the powder from the secondary ball milling is granulated with PVA, and the powder is pressed into a compact block green body using a tablet press according to the sintering conditions. The green body is sintered by debinding, the sintering temperature is 1200°C to 1400°C, and the holding time is 1h to 4h; 5) Crushing and grinding, using yttrium-stabilized zirconia ball mill, yttrium-stabilized zirconia grinding balls, and water as grinding media, with a ball-to-water ratio of 3:1:1 to 5:1:1, grinding until the average particle size of the powder is 1.0 μm to 5.0 μm, D90 ≤ 10 μm, and then drying for use; (2) Glass powder production method: Prepare the raw materials according to the requirements of glass powder components, mix them into glass, melt them at high temperature, purify them with water, and then ball-mill them to 1.0μm-5.0μm, and then dry them for use; (3) Preparation method of conductive silver paste: According to the component requirements of the conductive silver paste, the conductive porcelain powder, the flaky silver powder, the glass powder, the inorganic additive and the organic carrier are placed in a mixing device in proportion to mix the components evenly; the mixed slurry is fully ground and dispersed using a three-roll mill; The rolled slurry is filtered to remove impurities and is then prepared into conductive silver paste for automotive glass.

6. The black conductive silver paste for automobile glass according to claim 1, characterized in that: (1) The formula of the LSCO conductive ceramic powder is: ; (2) The formula of the glass powder is: 。 7. The method for preparing a black conductive silver paste for automobile glass according to claim 6, characterized in that: The specific method is: (1) Preparation of LSCO conductive ceramic powder 1) According to the formula of LSCO conductive ceramic powder, weigh the raw materials according to the total mass of 1 kg, put the raw materials, 3 kg φ10 mm zirconium oxide grinding balls, and 1 L of water into a 5 L zirconium oxide ball mill, mix for 24 hours, and then dry; 2) Pre-sintering of powders: the materials in 1) are placed in an alumina crucible and sintered in a box furnace at a heating rate of 100°C / h, a sintering temperature of 1050°C, and a holding time of 3.5h. After sintering, the powders are cooled in the furnace; 3) Secondary ball milling: the pre-sintered bulk powder was beaten into small pieces using a rubber hammer, and 3 kg of φ10 mm zirconium oxide grinding balls and 1 L of water were placed in a 5 L zirconium oxide ball mill, mixed for 48 hours, and then dried; 4) Granulation and briquetting: 10% PVA aqueous solution is used for granulation, the proportion of PVA solution is 15% of the powder, and the granulated porcelain powder is pressed into block green body by a tablet press at 20MPa / 15s; 5) Porcelain powder firing: the green body is sintered in a box furnace, and the binder removal curve is 100℃ / h to 600℃, and the temperature is kept for 6 hours to complete the binder removal, and then 300℃ / h to 1250℃, and the temperature is kept for 3 hours. After sintering, it is cooled with the furnace; 6) Crushing and grinding: the fired porcelain body is crushed into large-particle powders below 100 μm using a crusher, 3 kg φ10 mm zirconium oxide grinding balls and 1 L of water are placed in a 5 L zirconium oxide ball mill and mixed for 48 h ± 12 h, and the average particle size of the powder is controlled to be 2 μm to 3 μm; (2) Preparation of glass powder 1) Weigh the raw materials according to the formula of glass powder; 2) Glass melting, peak temperature 1300℃, heat preservation for 1h, water purification after sintering; 3) Grinding the glass powder: using a zirconia jar and zirconia grinding balls, the glass powder is ground to an average particle size of 2 μm to 3 μm; (3) Preparation of organic carrier The resin in the organic carrier is ethyl cellulose, and the organic solvent is a mixture of terpineol and butyl carbitol, with a ratio of 1:1; the ethyl cellulose, butyl carbitol and terpineol are heated and dissolved in a stirring and heating reactor until they are dissolved into a transparent state; the impurities and undissolved substances in the dissolved organic carrier are filtered out and then used for later use; (4) Requirements for flaky silver powder: the particle size of flaky silver powder is 1.0 μm to 10.0 μm, and the specific surface area is 1 m 2 / g~2m 2 / g, bulk density is 2g / ml~3g / ml, tap density is 3g / ml~4g / ml; (5) Preparation of conductive silver paste According to the formula of conductive silver paste: ; The raw materials are weighed according to a total mass of 1 kg, put into a stirring device for uniform dispersion, and then rolled into a conductive silver paste for automotive glass using a three-roll rolling mill. The fineness of the paste is controlled to be less than 10 μm, and the viscosity is 20 Pa•s to 60 Pa•s.

8. The method for preparing a black conductive silver paste for automobile glass according to claim 7, characterized in that: The formula of the conductive silver paste is: 。 9. The method for preparing a black conductive silver paste for automobile glass according to claim 7, characterized in that: The formula of the conductive silver paste is: 。 10. The black conductive silver paste for automobile glass according to claim 1, characterized in that: The conductive silver paste is printed on automobile glass, and after drying, it is sintered in a chain furnace with a peak temperature of 620° C. and a holding time of 200 s. After sintering, the conductive silver film has an adhesion of ≥20N, a black color, and a square resistance of 8 mΩ / □ to 15 mΩ / □.

Citation Information

Patent Citations

  • Grey conductive silver paste for automobile glass and preparation method thereof

    CN113539545A

  • Heated backlights

    US4728781A

  • Automotive glass thick film conductor paste

    US5296413A

  • Glass frits, a process for their production and their use in enamel barrier layers for stopping the migration of silver

    US5350718A

  • High durability low temperature lead-free glass and enamel compositions with low boron content

    US6624104B2